Pembentukan Portofolio Saham Optimal dengan Model Single Index pada Saham Bank Buku 4 yang Terdaftar di BEI Tahun 2024 - Ruzi, Fahrul (Jurnal Profiet, 2024)
This study was conducted to determine which bank book 4 stocks would be selected for the formation of a portfolio. The formation of this portfolio uses a single index model. This single index model was developed by William Sharpe and is a simplification of the Markowitz model that was previously developed by Markowitz. The results of this study provide information that the selected bank book 4 stocks are PNBN and NISP stocks with a portion of PNBN stocks of 85.9% and NISP stocks of 14.1%. The portfolio formed has an expected return of 3.7% with a portfolio risk of 7.18%. Keywords: Single Index Model, Portfolio, Return, Risk, Book Bank 4.